LEGITIMACY OF A SIRRI MARRIAGES (SECOND AND SO ON) BY THE PAIR OF CIVIL SERVANTS - Kusmayanti, Hazar; Ramadhanty, Nindya Tien (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
AbstrakPerkawinan siri di ketahui sebagai perkawinan di bawah tangan, artinya perkawinan yang memenuhi rukun dan syarat perkawinan serta tidak melanggar larangan-larangan perkawinan. Permasalahannya adalah ketika seseorang ingin beristri lebih dari seorang terdapat ketentuan yang harus dipenuhi. Penelitian ini bertujuan untuk menentukan keabsahan dan akibat hukum dari perkawinan siri (kedua dan seterusnya) yang dilakukan oleh pasangan PNS menurut PP Nomor 45 Tahun 1990 Tentang Izin Perkawinan dan Perceraian PNS dan Kompilasi Hukum Islam. Hasil dari penelitian ini perkawinan siri (kedua dan seterusnya) tidak sah menurut PP Nomor 45 Tahun 1990 Tentang Izin Perkawinan dan Perceraian PNS dan Kompilasi Hukum Islam. Sedangkan perkawinan siri (kedua dan seterusnya) sah menurut Hukum Islam. Kata kunci: KUA; Pegawai Negeri Sipil; perkawinanAbstractSirri Marriage are known as underhand marriages, meaning that marriages only fulfill the pillars and conditions of the marriage and do not violate marital restrictions. The problem is when someone wants to have more than one wife there are provisions that must be met. This study aims to determine the validity and legal consequences of perkawinan sirri (unregistered marriage) (second and so on) carried out by PNS couples according to PP No. 45 of 1990 concerning Marriage Permit and Divorce of Civil Servants and Compilation of Islamic Law. The results of this study of perkawinan sirri (unregistered marriage) (second and so on) are not valid according to Government Regulation No. 45 of 1990 concerning Marriage Permit and Divorce of Civil Servants and Compilation of Islamic Law. While perkawinan sirri (unregistered marriage) (second and so on) are legal according to Islamic Law.